2009
DOI: 10.1080/02713680802650377
|View full text |Cite
|
Sign up to set email alerts
|

Cyclooxygenase (COX)-Inhibiting Drug Reduces HSV-1 Reactivation in the Mouse Eye Model

Abstract: Bromfenac Na eye drops can suppress HSV-1 reactivation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 33 publications
0
14
0
Order By: Relevance
“…Gebhardt et al [56] reported that after hyperthermic stress, latently infected mice treated with celecoxib had less infectious virus on their ocular surfaces than controls (see Table 4). Higaki et al [58] reported that bromfenac sodium eye drops significantly reduced HSV-1 ocular shedding in mice induced by immunosuppression and hyperthermia. They concluded that bromfenac sodium eye drops could be a potent medication for suppressing HSV-1 reactivation [58].…”
Section: Mice and Hsv-1 Latencymentioning
confidence: 99%
“…Gebhardt et al [56] reported that after hyperthermic stress, latently infected mice treated with celecoxib had less infectious virus on their ocular surfaces than controls (see Table 4). Higaki et al [58] reported that bromfenac sodium eye drops significantly reduced HSV-1 ocular shedding in mice induced by immunosuppression and hyperthermia. They concluded that bromfenac sodium eye drops could be a potent medication for suppressing HSV-1 reactivation [58].…”
Section: Mice and Hsv-1 Latencymentioning
confidence: 99%
“…20 Regarding the therapeutic effect of bromfenac eye drops in animal models, it has been shown that they reduce retinal edema triggered by lipopolysaccharide systemic injection in iovs.arvojournals.org j ISSN: 1552-5783 rats and rabbits 9,17 and prevent reactivation of herpes virus 1 in infected mice. 21 Inflammation and edema are, as well, common responses to tissue damage or disease, as has been shown for the retina in animal models of glaucoma or optic nerve injury. [22][23][24][25][26][27][28] Macroglial retinal cells, astrocytes, and Müller cells readily respond to intravitreral injections, 29 injury, or disease.…”
mentioning
confidence: 99%
“…10 Although none of the three drug-treated groups showed any signifi cant differences from the saline solution group (P > 0.05, Welch's t test), the average copy number of viral DNA in the trigeminal ganglia of the mice treated with either etodolac or bromfenac Na eye drops was about one-tenth that of the mice treated with saline solution. However, the pranoprofen eye drops demonstrated an outcome inferior by an order of magnitude to that of the bromfenac Na eye drops in TGs.…”
Section: Resultsmentioning
confidence: 94%
“…Table 1 shows the eye swab results for the etodolac, bromfenac Na, and pranoprofen groups. 10 When the stimulation for reactivation was performed, ten of 24 eyes (41.7%) of the bromfenac Na group, fi ve of ten eyes (50.0%) of the etodolac group, and 17 of 25 eyes (68%) of the pranoprofen group showed positive results. However, compared with the results for the saline solution group (16 of 22 eyes, 72.7%), only the bromfenac Na group was signifi cantly different (P = 0.033, Fisher's exact probability test).…”
Section: Methodsmentioning
confidence: 95%
See 1 more Smart Citation